Magnesium intake and insulin resistance in obese adolescent girls - Harry Freitag Luglio Muhammad; Emy Huriyati; Rina Susilowati; Madarina Julia (Indonesian Pediatric Society Publishing House, 2009)
Background The worldwide increase in the prevalence of cardiovascular diseases in adulthood is related to obesity in children and adolescents. Insulin resistance and hyperinsulinemia observed in obese individuals are the precursors of cardiovascular diseases and type 2 diabetes mellitus. Magnesium, through its action on insulin receptors, is proposed to be an important factor in preventing insulin resistance. Objective The aim of this study was to assess the association between magnesium intake and insulin resistance in obese adolescent girls. Methods This was a cross-sectional study on obese adolescent girls in Yogyakarta, Indonesia. Insulin resistance was defined as a HOMA-IR index of3.16 or more. HOMA-IR was calculated using fasting insulin and plasma glucose levels. Magnesium intake and energy adjusted magnesium intake were measured using a 24-hour food recall method on 6 non-consecutive days. Results Of 7 8 obese adolescent girls included in our study, 56% of them were found to be insulin resistant. Magnesium intake was only 61 o/o of the recommended daily requirement for adolescent girls. There were no significant associations between magnesium intake and either HOMA-IR or hyperinsulinemia. Conclusion Our study does not find an association between insulin resistance and magnesium intake in obese adolescent girls.